2021
DOI: 10.3389/fendo.2021.768529
|View full text |Cite
|
Sign up to set email alerts
|

Causal Association of Coffee Consumption and Total, Knee, Hip and Self-Reported Osteoarthritis: A Mendelian Randomization Study

Abstract: BackgroundThe causal association between coffee consumption and the risk of OA is limited. This study was conducted to identify the potential causal effects of coffee consumption on total, knee, hip, and self-reported OA.MethodsGenome-wide association studies (GWAS) of OA were derived from the UK Biobank, comprising 50,508 participants of European ancestry (10,083 with cases and 40,425 controls), and genetic data for specific diagnosed knee OA (4462 cases and 17,885 controls), hip OA (12,625 cases and 50,898 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…One study discovered that individuals who consumed 2 to 4 cups of coffee daily exhibited lower levels of TSH concentrations. [5] However, it is important to note that this study did not establish a significant association between coffee consumption and the risk of developing hypothyroidism and hyperthyroidism. On the contrary, participation in physical exercise has been shown to have positive effects on individuals with hypothyroidism.…”
Section: Discussionmentioning
confidence: 58%
“…One study discovered that individuals who consumed 2 to 4 cups of coffee daily exhibited lower levels of TSH concentrations. [5] However, it is important to note that this study did not establish a significant association between coffee consumption and the risk of developing hypothyroidism and hyperthyroidism. On the contrary, participation in physical exercise has been shown to have positive effects on individuals with hypothyroidism.…”
Section: Discussionmentioning
confidence: 58%
“…The SNPs extracted from exposures (CHD, heart failure, stroke, IHD, and atrial fibrillation) were filtered by the following criteria: P < 5 × 10 –8 and linkage disequilibrium r 2 < 0.01 at a window size of 1 Mb. Further, the MR-Steiger method was performed on the left SNPs to calculate the variance explained by the exposure and outcome ( 18 ). The insignificant results of MR-Steiger indicated that the left SNPs may affect the outcome (i.e., ED) more than the exposure (i.e., CHD).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, individual SN P could be assessed for their influence on causal associations. The PhenoScanner database (version 2.0) was examined for each SNP ( 30 ) to determine whether existing risk factors have previously been associated with any significant associations ( P < 5 × 10 –8 ): BMI ( 31 , 32 ), previous knee injury ( 32 ), gout ( 33 ), coffee intake ( 12 ) for knee OA; Hip dysplasia ( 34 ), Steroids use ( 35 ), coffee intake ( 11 ) for hip OA; hypertension ( 33 ), diabetes, smoking ( 36 ) for RA; Vitamin D intake, Steroids use, smoking for OP ( 37 ). To rule out potential pleiotropic effects, we evaluated the effect of removing these SNPs from the MR estimations.…”
Section: Methodsmentioning
confidence: 99%
“…Habitual coffee consumption increases the incidence of OA ( 11 ), but not all joints. The effects of coffee were more prominent in knee OA, but not in the hip joint ( 12 ). Another Mendelian study found no causal effect of coffee consumption on the incidence of RA ( 13 ).…”
Section: Introductionmentioning
confidence: 99%